PERANCANGAN SISTEM PEMBERI MAKAN HEWAN BERBASIS IoT DENGAN SISTEM KONTROL ANDROID MENGGUNAKAN MVVM DAN CLEAN ARCHITECTURE - Joseph Sanjaya (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2022)
With the fast-paced world and the advancement of modern technology, the emergence of IoT has played an important role in every sector of our daily lives. In the field of home automation, it has played an important and pivotal role, it has made our lifestyle easier with the smart features inherited in automation including taking care of our pet. This paper gives a detailed hands-on IoT and how it can be implemented to presents a complete communication system to monitor dog feeders by checking their food, snacks, and water container data through a cloud-based server (Firebase Platform) using a micro-controller-based NodeMcu (Esp8266) and an android mobile application.